Tracking the Fate of Excess Li in the Synthesis of Various Liy[Ni1−xMnx]O2 Positive Electrode Materials Under Different Atmospheres. Issue 3 (1st March 2022) - Liu, Aaron; Phattharasupakun, Nutthaphon; Väli, Ronald; Ouyang, Dongxu; Dahn, J. R.
Abstract : Various Ni-rich Liy [Ni1−x Mnx ]O2 (x = ∼0.08, 0.2, 0.5) materials were synthesized with excess Li precursor in oxygen, dry air or air to understand what happens to the excess Li during synthesis. The Li[Ni1−x Mnx ]O2 components of the synthesized materials were single phase and synthesis in oxygen produced materials with less Ni in the Li layer. Inductively coupled plasma optical emission spectrometry (ICP-OES) and titration experiments on as-prepared samples and samples that were rinsed with water are useful in the determination of the amount of Li lost during heating, the amount of Li taken in by the material during synthesis and the amount of residual Li present in the samples as impurity phases. Materials synthesized in oxygen and dry air lost a similar amount of Li during heating but synthesis in air resulted in more Li loss. Synthesis in oxygen increased the lithium content, y, in the Liy [Ni1−x Mnx ]O2 materials. Materials with a higher Mn content can take in more Li to form Li-rich materials with larger values of y. From these experiments, the fate of Li can be tracked to heating loss, residual Li as impurity phases or uptake into the material as a function of Mn content and synthesis atmosphere.